Frühmittelalterlicher Halsschmuck mit Kreuzanhängern von der südwestlichen Krim - Chajredinova, Ėlʹzara Ajderovna ca. 20/21. Jh. (Mitteilungen zur christlichen Archäologie, 2017)
Archaeological materials played an important role for the studies of the history of Christianity in the South-Western Crimea. Especially interesting are individual artefacts of Christian cult, pectoral crosses in particular. Only women and girls wore these crosses in necklaces from 550-650 A.D. with crosses with flared ends. It was the earliest and the most popular type of crosses among the Crimean Goths. The location of beads and crosses documented in situ in graves provides arguments to reconstruct necklaces and costume which components they formed. Many necklaces contained several crosses, which could be explained as the understanding of cross as amulet. Crimean finds enlarge our notion of everyday Christian culture in the early mediaeval period, thus forming a striking evidence of close economic and cultural relations of the Crimea and the Byzantine Empire in the early Middle Ages.